(untitled) (Innovative professional education, 2023)
In the context of the reform of professional (vocational and technical) education in Ukraine, the introduction of standards for specific labor professions on a modular-competency basis, traditional approaches to the training of future qualified workers require revision, the form and methods of training need to be updated, and the introduction of modern pedagogical technologies is gaining relevance. One of such technologies is the case study technology, which enables future specialists to apply theoretical knowledge to solve practical tasks, promotes the development of independent thinking in them, the ability to listen to and take into account an alternative point of view, to express their own in a reasoned way. Fragments of specific examples of the use of educational cases during mastering the content of the modules of professional and theoretical training by future chefs are given. It is substantiated that the formation of the professional competence of the future chef is carried out more productively if educational cases are taken into account and implemented in the educational process.